Climate cover-up the crusade to deny global warming - Hoggan, James 1946- (Greystone Books, 2009)
This is a story of betrayal, selfishness, greed and irresponsibility on an epic scale. Hoggan examines the public relations circus that surrounds global warming, and uncovers the organized campaign, largely financed by the coal and oil industries, to make us think that climate science is still somehow controversial.